Sharia Compliance, Trust, and MSME Financial Inclusion in Indonesian P2P Lending - Dicky Wahyudi; Ernaldo Fikrul; Sharifurrohman Hoh (Ethiconomics: Journal of Islamic Banking and Finance, 2026)
Indonesian micro, small, and medium enterprises (MSMEs) face a persistent financing gap, while Islamic financial inclusion remains far below its conventional counterpart despite the country’s large Muslim population. Sharia peer-to-peer (P2P) lending has emerged as a potential bridge, yet empirical evidence on which platform dimensions actually drive MSME inclusion and through what mechanism remains scarce, as prior studies examine these dimensions in isolation. This study tests the simultaneous effects of three platform dimensions, business model quality, risk mitigation, and sharia compliance, on the financial inclusion of MSMEs, with trust as a mediating variable. Using an explanatory survey of 327 MSME actors across four sharia P2P lending platforms (ALAMI, Ammana, Qazwa, and Ethis) in Indonesia, the data were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4.0. All three dimensions significantly and positively affect MSME financial inclusion, with sharia compliance the strongest driver (β = 0.297; p < 0.001), followed by risk mitigation (β = 0.265) and business model quality (β = 0.218). Trust partially mediates these relationships, and the model explains 68.3% of the variance in MSME financial inclusion (R² = 0.683). The findings indicate that substantive, not merely formal, sharia compliance is the primary lever for deepening MSME inclusion, providing regulators and platform operators with an evidence-based priority for strengthening the sector following POJK 40/2024.